Accounting and control of indebtedness according to electronic payments of food industry enterprises using information and communication technologies - Muravskyi, Volodymyr; Khoma, Nadiia; Kalyn, Roman; Reveha, Oleh (Herald of Economics, 2023)
Introduction. Digitization of socio-economic processes and the implementation of modern information and communication technologies in the currency and banking sphere have led to the evolution of the methodology of electronic settlements with counterparties. The latest stage in the development of electronic transaction systems is the information integration of counterparties into a single information environment of business relationships based on the principles of blockchain technology.Purpose. The purpose of the article is to research the peculiarities of the organization of accounting and control of electronic payments and improvement of their methodology in the context of debt repayment in the conditions of the use of information and communication technologies.Methods. Systemic, innovative, functional approaches and methods of generalization, bibliographic and comparative analysis were used in the process of realizing the established goal of scientific research.Results. It is proved that the fundamental basis of the system of electronic transactions are electronic contracts, which form a database for the digitization of accounting and control processes. A list of permanent and variable accounting data provided by the electronic payment system and the company’s divisions for the digitization of accounting for the occurrence and repayment of receivables and payables is proposed. The procedure for internal control of payment discipline and external independent control (confirmation) of business reliability and solvency has been improved with the notification of all counterparties interested in cooperation. A methodology for rating counterparties based on the reliability criterion has been developed to automate accounting for the formation and use of the reserve of doubtful debts. The possibility and expediency of alternate automatic mutual offsetting of receivables and payables between all counterparties of food industry enterprises based on accounting information based on previously executed smart contracts is substantiated. Mutual repayment of debt in the system of electronic transactions contributes to the minimization of the overall level of debt in the economic systems of the association of enterprises of food industry, cities, regions, etc.Discussion. The automatic offsetting of indebtedness ensures the formation of the phenomenon of debt-free (minimally debt) activity of food industry enterprises, which is an important element of the formation of a post-industrial economy and an optimization society, in which all socio-economic processes are adapted to the needs of people, which is the subject of subsequent scientific research.